In meeting the increasing demands for total knee arthroplasty, can we achieve high levels of quality care in a small community hospital? A mixed-methods study - Sanders, Ethan B.; Dobransky, Johanna S.; Chen, Brian P.; Bodrogi, Andrew W.; , on behalf of Ottawa Arthroplasty Group; Beaulé, Paul E.; Poitras, Stéphane (Frontiers in Surgery, 2023)
Purpose Small community hospitals (SCHs) help meet the demand for total knee arthroplasty (TKA). This mixed-methods study compares outcomes and analyses of environmental differences following TKA at a SCH and a tertiary care hospital (TCH). Methods Quantitative: A retrospective review of 352 propensity-matched primary TKA procedures at both a SCH and a TCH, based on age, body mass index, and American Society of Anesthesiologists class, was completed. Groups were compared by length of stay (LOS), 90-day emergency department visits, 90-day readmissions, reoperations, and mortality. Qualitative: Based on the Theoretical Domains Framework, seven prospective semistructured interviews were performed. Interview transcripts were coded and belief statements were generated and summarized by two reviewers. Discrepancies were resolved by a third reviewer. Results Quantitative: The average LOS for the SCH was significantly shorter than that for the TCH (2.0 ± 0.2 vs. 3.6 ± 2.7 days; p < 0.001), a difference that persisted following a subgroup analysis of ASA I/II patients (2.0 ± 0.2 vs. 3.2 ± 2.2; p < 0.001). There were no significant differences in other outcomes. Qualitative: The main themes that revolved around a higher case load for physiotherapy at the TCH resulted in patients waiting longer to be mobilized after surgery. Patient disposition also affected their discharge rates. Conclusion Given the increasing demand for TKA, the SCH represents a viable option to increase capacity, while reducing LOS. Future directions to reduce LOS include addressing social barriers to discharge and patient prioritization for assessment by allied health services. When TKA is performed by the same set of surgeons, the SCH provides quality care with a shorter LOS and comparable with urban hospitals, and this can be attributed to the differences in resource utilization in the two hospital settings.